63=9(2-w)

Simple and best practice solution for 63=9(2-w) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63=9(2-w) equation:


Simplifying
63 = 9(2 + -1w)
63 = (2 * 9 + -1w * 9)
63 = (18 + -9w)

Solving
63 = 18 + -9w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '9w' to each side of the equation.
63 + 9w = 18 + -9w + 9w

Combine like terms: -9w + 9w = 0
63 + 9w = 18 + 0
63 + 9w = 18

Add '-63' to each side of the equation.
63 + -63 + 9w = 18 + -63

Combine like terms: 63 + -63 = 0
0 + 9w = 18 + -63
9w = 18 + -63

Combine like terms: 18 + -63 = -45
9w = -45

Divide each side by '9'.
w = -5

Simplifying
w = -5

See similar equations:

| 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 | | 6n=64 | | 4.6x-14.6=5.4 | | 2(n+n+1)=(n+2)-36 | | 3/5x-2=1/5 | | 10y(y+2)+3x=5(3-x) | | 4y-2(x-y)= | | 5x-3x+16=-x+8 | | 9w-8=64 | | 5.50-3.75= | | 8+2x+3-x=2+1 | | (3/x)-2=11 | | J-62/4=5 | | -6x+-9=1 | | 4s-10=6 | | 8k-5= | | 6(w-1)=2w+4-2(-4w-2) | | -4n+7=1 | | 35=4y+y | | 3x+4(x+y)= | | 9+23= | | -3+8=5a+24 | | P/4-1=2 | | -61=8-4w+-14-w | | -2(2u-7)+3u=3+3(5u-1) | | 1/6b=9.2 | | 8p(p-10)=0 | | 5x=3x-10+2x | | 3y-6x+12=-6 | | 1/9b=9.2 |

Equations solver categories